THE USE OF PEER REVIEWING IN OVERCOMING PHONOLOGICAL ERRORS IN ENGLISH PRONUNCIATION - Ira Adinegara; A. M. Surachmat; Didih Faridah (JALL (Journal of Applied Linguistics and Literacy), 2019)
ABSTRACT This study reports on the use of peer reviewing in overcoming phonological errors in English pronunciation conducted to the freshmen of English Education Program in Galuh University. Peer review is one of appropriate techniques to support students in learning speaking particularly English pronunciation. In this regard, the writers addressed some questions: 1) How does the lecturer use peer review technique in overcoming phonological errors in performing English pronunciation?, 2) What are the students’ perceptions toward the use of peer review technique in overcoming phonological errors in performing English pronunciation?, and 3) What are the benefits of peer review technique in overcoming phonological errors in performing English pronunciation?. Related to the research questions, the writers adopted qualitative approach particularly a case study as the research design. The writers conducted classroom observation, interview to an English lecturer and six students and administered a questionnaire to the students as well. In this case, the respondents were selected purposively. The results showed that the use of peer review is useful to support and motivate the students to learn well. By using peer review, students can be active in their process learning and also they can improve their critical thinking in speaking particularly in overcoming phonological errors in performing English pronunciation.Keywords: peer review, pronunciation